EVALUATION OF DIFFERENT SYNTHETIC AND NATURAL POLYMERS AS PROTECTIVE LAYER ON HIGHLY SOLUBLE AND HIGH DOSE DRUG METOPROLOL SUCCINATEFOR MANUFACTURING OF CONTROL RELEASE MULTI UNIT PELLETS TABLETS - Borra, Syam Prasad; Eswaraiah, M. Chenna; Reddy, G. Kamalakar (International Journal of Applied Pharmaceutics, 2018)
Objective: Evaluation of different natural and synthetic polymers as protective layer (PL) in the manufacturing of control release (CR) multi-unit pellets (MUPS) tablets, highly soluble and high dose drug metoprolol succinate (MS) was selected as model drug. The function of PL is to protect CR functional coating layer of pellets from damage during compression of MUPS tablets. Â  Methods: MS is highly soluble biopharmaceutics classification system(BCS) Classâ€“I molecule, hence selected aqueous solution layering method for drug loading in fluid bed processor (FBP), optimized formulation was manufactured by using seal coating on microcrystalline cellulose (MCC) pellets followed by drug loading (DL) and CR coating, applied by using the solution layering method in FBP. Given coating on these functional coated pellets with different natural and synthetic polymers like hydroxypropyl cellulose (Klucel LF), polyethylene glycol 6000 (PEG 6000), hypromellose 5 cps (HPMC 5cps), guar gum (GG) and xanthan gum (XM). Evaluated these pellet's for physical characterization and chemical characterization. Results: Drug release profiles of CR MUPS tablets containing PL coating were compared to those CR pellets and f2 values observed was 81.83, 49.92, 89.35, 66.44, and 85.25 with Klucel LF, PEG 6000, HPMC 5 cps, GG and XM coated MUPS tablets respectively. The dissolution data indicated that, there was no significant change were observed with MUPS containing Klucel LF, HPMC 5 cps, GG and XG PLs whereas faster release profiles were observed with PEG 6000PL MUPS tablets. Conclusion: Based on these dissolution profiles it was concluded that by applying low viscous natural or synthetic binders like Klucel LF, HPMC 5 cps, GG and XG on functional coating pellets given good protection to functional coating pellets from damage during compression. It is a very effective and potent strategy for manufacturing of MUPS tablets. Whereas PEG 6000 polymer not able to give protection to functional coating pellets from damage during compression, it may be due to its very low viscosity of PEG 6000.